Experience of Emergency Department Patients With Using the Talking Pole Device: Prospective Interventional Descriptive Study - Yoo, Junsang; Soh, Ji Yeong; Lee, Wan Hyoung; Chang, Dong Kyung; Lee, Se Uk; Cha, Won Chul (JMIR Publications, 2018)
BackgroundPatient engagement is important. However, it can be difficult in emergency departments (EDs). ObjectiveThe aim of this study was to evaluate the satisfaction of ED patients using a patient-friendly health information technology (HIT) device, the "Talking Pole," and to assess the factors relevant to their satisfaction. MethodsThis study was conducted in May 2017 at the ED of a tertiary hospital. The "Talking Pole" is a smartphone-based device attached to a intravenous infusion pole with sensors. It is capable of sensing patient movement and fluid dynamics. In addition, it provides clinical information from electronic medical records to patients and serves as a wireless communication tool between patients and nurses. Patients and caregivers who entered the observation room of the ED were selected for the study. The "Talking Pole" devices were provided to all participants, regardless of their need for an intravenous pole upon admittance to the ED. After 2 hours, each participant was given an 18-item questionnaire created for this research, measured on a 5-point Likert scale, regarding their satisfaction with "Talking Pole." ResultsAmong 52 participants recruited, 54% (28/52) were patients and the remaining were caregivers. In total, 38% (20/52) were male participants; the average age was 54.6 (SD 12.9) years, and 63% (33/52) of the participants were oncology patients and their caregivers. The overall satisfaction rate was 4.17 (SD 0.79 ) points. Spearman correlation coefficient showed a strong association of "overall satisfaction" with "comparison to the previous visit" (ρ=.73 ), "perceived benefit" (ρ=.73), "information satisfaction" (ρ=.70), and "efficiency" (ρ=.70). ConclusionsIn this study, we introduced a patient-friendly HIT device, the "Talking Pole." Its architecture focused on enhancing information delivery, which is regarded as a bottleneck toward achieving patient engagement in EDs. Patient and caregiver satisfaction with the "Talking Pole" was positive in the ED environment. In particular, correlation coefficient results improved our understanding about patients' satisfaction, HIT devices, and services used in the ED.